Fractional re-distribution among cell motility states during ageing - Jude M. Phillip (Nature Portfolio, 2021)
Phillip and colleagues use dermal fibroblasts from a range of donors to quantify cell motility in ageing cells. They show that the age-dependent decrease in cell motility is not due to the reduced motility of all cells, but results from the fractional redistribution among motility states.